2019
DOI: 10.1136/bmj.l6131
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of labour at 41 weeks versus expectant management and induction of labour at 42 weeks (SWEdish Post-term Induction Study, SWEPIS): multicentre, open label, randomised, superiority trial

Abstract: ObjectiveTo evaluate if induction of labour at 41 weeks improves perinatal and maternal outcomes in women with a low risk pregnancy compared with expectant management and induction of labour at 42 weeks.DesignMulticentre, open label, randomised controlled superiority trial.Setting14 hospitals in Sweden, 2016-18.Participants2760 women with a low risk uncomplicated singleton pregnancy randomised (1:1) by the Swedish Pregnancy Register. 1381 women were assigned to the induction group and 1379 were assigned to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
108
6
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 34 publications
(50 reference statements)
9
108
6
6
Order By: Relevance
“…But at the same time in day-to-day clinic these women often need or even ask for induction of labor. However, there were only few data regarding this patient group [19].…”
Section: Discussionmentioning
confidence: 99%
“…But at the same time in day-to-day clinic these women often need or even ask for induction of labor. However, there were only few data regarding this patient group [19].…”
Section: Discussionmentioning
confidence: 99%
“…registry-based randomized controlled trials 20. In the era of Big Data, medical researchers and health authorities have become increasingly dependent on the ICD-coding system for tracking patterns in obstetric-related morbidities.…”
mentioning
confidence: 99%
“…Giving clear unbiased information to pregnant women enabling them to make their own choices is extremely important. For those with late term pregnancies a new trial reported by Wennerholm and colleagues (doi:10.1136/bmj.l6131) suggests that waiting longer than 41 weeks to induce labour increases the risk of perinatal mortality 1…”
mentioning
confidence: 99%